Struktur dan Nilai Religius dalam Novel Rinai Kabut Singgalang Karya Muhammad Subhan - Deswika, Silvia; Abdurahman, Abdurahman; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This article aimed to describe: (1) the structure of the novel Rinai Kabut Singgalang, by Muhammad Subhan, and (2) the religious values found in this novel. The data of this study were the texts of the novel that contain religious valuesâ€‹.Those data were collected descriptively through some stages, (1) read and mark the events and the charactersâ€™ behaviors which lead to the focus of the research, (2) mark parts of the novel that became the focus of research, and (3) record the data by noting down those which are related to the religious valuesâ€‹â€‹. The findings of the study were first, the plot of the novel moves forward, the main character is Fikri, the background of the novel is the setting of a place. The theme of this novel is an unrequited love, and the message is to surrender to Allah and be patient in facing the temptations. Second, the religious values found â€‹â€‹in this novel â€œRinai Kabut Singgalangâ€ by Muhammad Subhan are (a) the values of aqidah which are believing in Allah, believing that both in life and death humans always come back to God, believing that in every difficulty Â Allah will show an easy way to face it, believing that sustenance, mate and death are all decided by Allah, and believing in qadha and qadhar. (b) the values of Islamic shariah which are salat, fasting, prayer, dzikir and syahadat, Islamic theology learning, and the Qur'an reading. (c) moral values â€‹â€‹which consist of asking forgiveness to Allah, saying assalamualaikum, saying hamdallah, being grateful towards Allah, nurturing good relationships, maintaining trust, praying for those who have died, helping people in need, respecting the values â€‹â€‹and norms in society, being dutiful to parents, maintaining purity, gentleness and courtesy, being always steadfast and patient in facing the temptations of Allah.